Belonging Canadians: Minority stereotypes and Korean-Canadian adolescents' discursive constructions of health and fitness - Kim, Kyoung-Yim (University of Ottawa (Canada), 2004)
This thesis focuses on the ways in which Korean-Canadian youth construct their own understandings of health and fitness and introduce health and fitness practices into their daily lives. Grounded theory is used for an analysis of in-depth conversations with 9 Korean-Canadian adolescents. Results show how these young people appropriate elements of dominant Western health discourses to elaborate their own constructions of health and fitness. These constructions are racialized and gendered, and they speak of the importance of bodily shape and appearance. Furthermore, these constructions point to the high amount of school-related pressure and stress that seem to be part of the day-to-day lives of these adolescents. In that sense, health and fitness practices are very costly for Korean-Canadian adolescents in terms of money, time and self-discipline, but they are valuable to them as they are perceived as ways to successfully integrate Canadian culture, as ways to "belong."
Keywords: Health Sciences, Public Health.